The Ability of Benzoic Acid to Reduce Cr(VI) Heavy Metal Content in Aqueous Solution - Anugrah Windy Mustikarini; Barlah Rumhayati; Candrawati Cahyani (Chemistry Department, The University of Brawijaya, 2015)
Chromium (VI) is an ionic heavy metal which has to be handled properly when dissolved in water due to its toxicity, corosive, carsinogenic activity.. According to the State Minister for Population and Environment’s regulation, the quality standards of waste water, which is allowed to be discharge on surface water contains Cr(VI) is 0.05-1 mg/L. This research used benzoic acid which is a kind of organic acid to reduce Cr(VI) content in water. Benzoic acid has an active carboxyl group which interact this metal. This paper, the elimination of Cr(VI) using benzoic acid is undertaken through pH adjustment by regulating with phosphoric acid. The result showed the best condition to reducing Cr(VI) content 41.99% when 400 ppm of benzoic acid and pH 7 was applied, respectively.